A comparative study on efficacy of metoprolol and ivabradine in acute ST elevation myocardial infarction patients - Gurrala, Rajashekar Reddy; Unni, Vinod K.; Kadloor, Parvaiz; Rayees, T. K. Mohammed; Razvi, Syed Azeemuddin; Uzma, Syeda; Fatima, Mehruq (International Journal of Research in Medical Sciences, 2019)
Background: The ST-elevation myocardial infarction (STEMI), a fatal disease, is rapidly extending in patients, worldwide. Therefore, proper and timely diagnosis followed by appropriate management becomes necessary. The study aimed to compare the effectiveness of metoprolol and ivabradine in acute STEMI patients. Methods: This was an observational, comparative, in-hospital study carried out in patients admitted in the in-patient cardiac department, intensive cardiac care unit of a tertiary care centre in India. Total 60 patients diagnosed with acute ST-elevation MI were included in the study and were equally divided into two groups. Group 1 involved patients who were given metoprolol for treatment and group 2 involved patients who were given ivabradine. The patients were assessed in terms of heart rate, NYHA class, and ejection fraction. Follow-up of 30 days was taken in all patients. Results: Ivabradine reduced mean heart rate from 85.57 bpm at baseline to 78.23 bpm. Heart rate in the metoprolol group was reduced from 81.93 bpm to 76.47 bpm over the same time period. Metoprolol and ivabradine showed significant improvement in the ejection fraction volume during the in-hospitalization stay. Ivabradine showed a better improvement in ejection fraction when compared to metoprolol but the difference was not found to be statistically significant. Higher mortality was assessed in ivabradine group compared to metoprolol. Conclusions: The study gives the gold standard efficacy and mortality benefit of metoprolol, although ivabradine on the other hand gave better responses in heart rate reduction and improvements in ejection fraction.